Nutritional concerns in recreation, exercise, and sport - Driskell, Judy A. [ (Judy Anne)]; Wolinsky, Ira (CRC Press, 2009)
Athletes, coaches, and recreationalists are continually seeking ways to maximize their competitive efforts in both exercise and sport. This title covers the major nutritional concerns related to physical activity and the serious recreationalist and athlete, focusing on core questions in the growing field of sports nutrition.